Leaders Need to Be Led: Complementary Followership through Interchangeable Roles among Leader-Follower Positions - Lee, Junesoo; Kim, Booyuel; Chung, Jongwoo (KDI School of Public Policy and Management, 2021)
Leadership is often recognized as a major driver for successful team effectiveness. However, even weak leadership may show good team performance, and it is worth studying how weak leadership can be helped and complemented by followership. To investigate this paradoxical mechanism behind leadership-followership practices, we examined (1) multi-dimensional figures of leadership and followership using the multifactor leadership questionnaire (MLQ), and (2) the impacts of the combinations of leadership and followership on team performances both during and after a community-driven development (CDD) program. To that end, this study examined a rural CDD case implemented by the Korea International Cooperation Agency (KOICA) and the Myanmar Ministry of Agriculture, Livestock, and Irrigation (MOALI). The CDD leaders of 100 villages (and randomly selected residents of each village) were surveyed. And the collected data were analyzed using regression analysis method. The analyses present some common patterns of how weak leadership and strong followership can lead to better performance than other combinations of leadership and followership. First, the W-S state (Weak leadership and Strong followership) could be better for CDD performances than S-S (Strong leadership and Strong followership) and S-W (Strong leadership and Weak followership). This means that W-S is a necessary condition for successful group performance, which implies that having weak leadership can be an opportunity for strengthening followership. In detail, from the followers’ perspective, strong followership in some factors (intellectual stimulation, individualized consideration, and contingent reward) may best complement weak leadership in the same factors during CDD program. For the sustainability of community development, followership in idealized influence (i.e., trustful dedication) can help complement weak leadership so as to sustain community development even after the CDD program completed. Second, strong leadership could be detrimental to CDD performances because there were some negative impacts of S-S (Strong leadership and Strong followership) and S-W (Strong leadership and Weak followership). We conclude with theoretical and practical conditions of “complementary followership” i.e., the complementary combinations of leadership and followership in group performance.
Keywords: Leadership; Followership; Community-driven Development